Cutting edge: Blockade of inhibitor of apoptosis proteins sensitizes neutrophils to TNF- but not lipopolysaccharide-mediated cell death and IL-1β secretion - Chen, K; Lawlor, K; von Pein, J; Boucher, D; Gerlic, M; Croker, B; Bezbradica, J; Vince, J; Schroder, K (American Association of Immunologists, 2018)
The mammalian inhibitor of apoptosis proteins (IAPs) are key regulators of cell death and inflammation. A major function of IAPs is to block the formation of a cell death–inducing complex, termed the ripoptosome, which can trigger caspase-8–dependent apoptosis or caspase-independent necroptosis. Recent studies report that upon TLR4 or TNF receptor 1 (TNFR1) signaling in macrophages, the ripoptosome can also induce NLRP3 inflammasome formation and IL-1β maturation. Whether neutrophils have the capacity to assemble a ripoptosome to induce cell death and inflammasome activation during TLR4 and TNFR1 signaling is unclear. In this study, we demonstrate that murine neutrophils can signal via TNFR1-driven ripoptosome assembly to induce both cell death and IL-1β maturation. However, unlike macrophages, neutrophils suppress TLR4-dependent cell death and NLRP3 inflammasome activation during IAP inhibition via deficiencies in the CD14/TRIF arm of TLR4 signaling.